RAMOS, Danilo Paiva. Círculos de Coca e Fumaça. São Paulo: Hedra, 2018. 543p. - Cardoso, Gabriel Novais (Ilha Revista de Antropologia, 2019)
RAMOS, Danilo Paiva. Círculos de Coca e Fumaça. São Paulo: Hedra, 2018. 543p.